Development and validation of panoptic Meso scale discovery assay to quantify total systemic interleukin‐6. (4th June 2015) - Chaturvedi, Shalini; Siegel, Derick; Wagner, Carrie L.; Park, Jaehong; van de Velde, Helgi; Vermeulen, Jessica; Fung, Man‐Cheong; Reddy, Manjula; Hall, Brett; Sasser, Kate
<x xml:space="preserve">Abstract</x> Aim Interleukin‐6 (IL‐6), a multifunctional cytokine, exists in several forms ranging from a low molecular weight (MW 20–30 kDa) non‐complexed form to high MW (200–450 kDa), complexes. Accurate baseline IL‐6 assessment is pivotal to understand clinical responses to IL‐6‐targeted treatments. Existing assays measure only the low MW, non‐complexed IL‐6 form. The present work aimed to develop a validated assay to measure accurately total IL‐6 (complexed and non‐complexed) in serum or plasma as matrix in a high throughput and easily standardized format for clinical testing. Methods Commercial capture and detection antibodies were screened against humanized IL‐6 and evaluated in an enzyme‐linked immunosorbent assay format. The best antibody combinations were screened to identify an antibody pair that gave minimum background and maximum recovery of IL‐6 in the presence of 100% serum matrix. A plate‐based total IL‐6 assay was developed and transferred to the Meso Scale Discovery (MSD) platform for large scale clinical testing. Results The top‐performing antibody pair from 36 capture and four detection candidates was validated on the MSD platform. The lower limit of quantification in human serum samples (n = 6) was 9.77 pg l–1, recovery ranged from 93.13–113.27%, the overall pooled coefficients of variation were 20.12% (inter‐assay) and 8.67% (intra‐assay). High MW forms of IL‐6, in size fractionated serum samples from myelodysplastic syndrome and rheumatoid arthritis patients, were detected by the assay but not by a commercial kit. Conclusion This novel panoptic (sees all forms) IL‐6 MSD assay that measures both high and low MW forms may have clinical utility.